2010
DOI: 10.33336/aik.93854
|View full text |Cite
|
Sign up to set email alerts
|

Sukupolvivastuu ja syyllisyys

Abstract: ”Nykyinen keski-ikäinen perhesukupolvi on sukupolvivastuiden osalta … varsin ongelmallisessa tilanteessa. Se elää usein kaukana vanhemmasta sukupolvesta, erilaisessa kulttuuris-sosiaalisessa maailmassa, ja joutuu tekemään ratkaisuja edelleen vallitsevan perhevastuiden ideaalimallin ja käytäntöä hallitsevan tosiasiamallin välillä.” (Marin 2005, 257) Tällaisessa paineisessa tilanteessa on keskeistä tutkia, millaisen puheen avulla keski-ikäiset rakentavat sukupolvivastuutaan eli miten puhutaan huolenpidosta omist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Further, we have shown that the teaching material and their graphical models strive to make these representations (1) concrete for teachers and (2) more relatable for young students. However, there are different emphases in the representation of narrative genre within the PRF, which either perpetuate focus on macrostructure in the curriculum (see Eriksson & Sahlin 2015a, 2015b or reframe the main focus (see Grönte, 2013 ) of narrative genre. The graphical models further contribute to reshaping these different recontextualisations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we have shown that the teaching material and their graphical models strive to make these representations (1) concrete for teachers and (2) more relatable for young students. However, there are different emphases in the representation of narrative genre within the PRF, which either perpetuate focus on macrostructure in the curriculum (see Eriksson & Sahlin 2015a, 2015b or reframe the main focus (see Grönte, 2013 ) of narrative genre. The graphical models further contribute to reshaping these different recontextualisations.…”
Section: Discussionmentioning
confidence: 99%
“…This change in emphasis compared to the text material exemplifies graphical models as being limited to representing a narrow selection of narrative aspects (see Riley & Reed, 2005 ;Thorsten, 2019 ;Wray & Lewis, 1997 ) as scaffolds and representations of schemata (see Emmott et al, 2009 ;McCutchen, 2006 ). Indeed, the textbooks feature alternative models to, for example, describe characters (see Eriksson & Sahlin, 2015a ;Grönte, 2013 ). The visual foregrounding of obstacle and solution aligns with the curricula's emphasis on elements of text structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation